Mechanochemical-assisted hydrolysis of pretreated rice straw into glucose and xylose in water by weakly acidic solid catalyst. (February 2019) - Qi, Xinhua; Yan, Lulu; Shen, Feng; Qiu, Mo
Graphical abstract: Highlights: Weak acid solid catalyst prepared by pyrolysis of lignin and KOH from black liquor. Mechanochemical pretreatment of catalyst and substrate gave high hydrolysis yields. 76.3% glucose yield was achieved from cellulose in 0.015 wt% HCl aqueous solution. The catalyst showed good stability and recyclability in the aqueous reaction system. A promising process for the comprehensive utilization of lignocellulosic biomass. Abstract: In this work, carbonaceous materials bearing only weakly acidic COOH and phenolic OH groups were directly prepared by the pyrolysis of lignin and KOH in black liquor generating from rice straw that was pretreated with KOH aqueous solution. The synthesized carbon materials were used for the hydrolysis of cellulose or the alkali pretreated rice straw in water, after mixed ball-milling pretreatment, and provided a high glucose yield of 76.3% for cellulose, high yields of 52.1% glucose and 66.5% xylose for alkali pretreated rice straw, respectively, in 0.015 wt% HCl aqueous solution at 200 °C for 60 min. The weakly acidic catalyst showed good stability and recyclability in the aqueous reaction system. This work provides an efficient process for the hydrolysis of lignocellulose by biomass-derived weakly acidic catalysts in water and should have wide applications in biomass utilization.